2016
DOI: 10.31219/osf.io/b4cxt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mixed Emotions: Network Analyses of Intra-Individual Co-occurrences Within and Across Situations

Abstract: This study revisits the structure of emotions by employing a co-occurrence network analysis. While previous studies have examined the structure of emotions primarily through inter-individual correlations, we investigated how often and which specific positive and negative emotions occur together within individuals. Two studies were conducted with high school students, one (N=21,678) using retrospective emotion measures (open-ended questions and 28 rated items) and the other (N = 471) using in-the-moment emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, we report ratings for the two feelings that had been mentioned most frequently in the open-ended responses, namely stressed and bored. Seventeen additional academic and social feelings were assessed and reported elsewhere (Moeller et al, 2018;White et al, 2017), but are not addressed in this study. For a justification of the item selection for the survey and this article, please see the supplemental materials on pages 8ff.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we report ratings for the two feelings that had been mentioned most frequently in the open-ended responses, namely stressed and bored. Seventeen additional academic and social feelings were assessed and reported elsewhere (Moeller et al, 2018;White et al, 2017), but are not addressed in this study. For a justification of the item selection for the survey and this article, please see the supplemental materials on pages 8ff.…”
Section: Methodsmentioning
confidence: 99%
“…They also observed that individuals experienced more than one emotion at the same time. Indeed, 33% of the time, individuals experienced at least one positive and one negative emotion simultaneously (cf., Moeller, Ivcevic, Brackett & White, 2018). Taken together, such findings make it hard to draw any definitive conclusions regarding the typology of boredom from the Goetz et al study.…”
Section: The Issue Of Arousalmentioning
confidence: 99%
“…Even though each emotion may have a distinct mechanism, emotions are not entirely independent of each other. Specifically, in daily life, people frequently experience blends of distinct emotions (Scherer et al, 2004) that can even be of opposite valence (Larsen & McGraw, 2014; Moeller et al, 2018; Trampe et al, 2015). Moreover, some theorizing argues that nonbasic emotions (e.g., shame , guilt ) are constructed from or accompanied by basic emotions (Oatley & Johnson-Laird, 1987).…”
Section: Conceptualizations Of Emotionsmentioning
confidence: 99%
“…Moreover, if causal networks of different emotions overlap, the amount of overlap could be a predictor of the probability that these emotions co-occur. So far, research documents that emotions co-occur frequently (e.g., Larsen & McGraw, 2014; Moeller et al, 2018; Scherer et al, 2004; Trampe et al, 2015), but it is less clear how this comes about. From the current perspective, activation of the causal network representing one distinct emotion may spread via shared nodes to causal networks representing other distinct emotions.…”
Section: Theoretical Implications and Future Research Directionsmentioning
confidence: 99%